SONGS AS A TOOL FOR PRONUNCIATION TEACHING - Abdug'aniyeva Durdona; Zulfiya Axmedova (TADQIQOTLAR, 2026)
Annotation: In recent years, the teaching of English pronunciation has received increasing attention as a crucial component of effective communication. Accurate pronunciation not only enhances intelligibility but also boosts learners’ confidence and overall language competence. However, many learners face challenges in mastering pronunciation due to the complexity of English phonetics, differences from their native language, and limited exposure to authentic spoken input. Songs have emerged as an innovative and effective tool for pronunciation teaching. They provide authentic language input in a natural and enjoyable context, exposing learners to rhythm, stress, intonation, and connected speech. Unlike traditional drills and repetitive exercises, songs engage learners cognitively and emotionally, fostering both phonetic awareness and motivation. Singing along allows students to internalize pronunciation patterns subconsciously, practice fluency, and develop a more natural-sounding speech. Furthermore, songs facilitate social interaction, collaboration, and creative expression in the classroom, aligning with contemporary theories of language acquisition. They cater to different learning styles, activate multiple intelligences, and create a positive, low-anxiety learning environment. This makes songs a versatile pedagogical tool that not only improves pronunciation but also enhances learners’ overall engagement and enjoyment in the language-learning process. This study aims to explore the effectiveness of songs as a tool for teaching English pronunciation, focusing on their impact on learners’ phonetic development, motivation, and classroom interaction. The findings are expected to provide practical insights for educators seeking innovative and enjoyable strategies to improve pronunciation instruction.